FEC Methods’ Effects on Intelligent Video Streaming Over 2.4 GHz Wireless Channels: An Analysis - Khalil, Noor Mohammed; Merzah, Hana: Hanaa Hameed (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The increased usage of portable and cellular devices in recent decades has made streaming videos over wireless networks more challenging. The 2.4 GHz wireless channels’ non-linear nature causes erratic video transmission due to interference from other wireless devices and general channel noise. Jitter can result from network issues and uncorrected data loss at the decoder, leading to packet loss. MPEG-compressed videos require significant bandwidth, posing another challenge. To address this, a model was introduced to measure MPEG-4 video streaming with forward error correction (FEC) efficiency in wireless local area networks (WLANs) using IEEE 802.11 Distributed Coordination Function (DCF). The model considers the pattern of packet loss in the wireless network, including diffused packet loss and packet loss. Simulation results show that the suggested approach has higher throughput and reduced packet loss compared to the current technique.